Implementasi Kegiatan Market Day untuk Menumbuhkan Jiwa Kewirausahaan Siswa Kelas V di SDN 1 Gunungkeling - Nida Bismillah; Agatha Kristi Pramudika Sari (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to identify the activities of Market Day in fostering entrepreneurial spirit among fifth-grade students at SDN 1 Gunungkeling using the one group pretest-posttest method. The population in this study comprises all students of SDN 1 Gunungkeling. The sample consists of 30 students selected using simple random sampling. Before the implementation of Market Day, students were given an entrepreneurial spirit questionnaire to measure their level of entrepreneurship. After the activity, students were given the same entrepreneurial spirit questionnaire to evaluate changes. Data were analyzed using SPSS version 27. Prior to conducting the t-test, the data underwent preliminary assessments to ascertain its suitability for the test, specifically normality and homogeneity tests. After the prerequisite tests, the data were analyzed using the paired-samples T-test. This result indicate a statistically significant impact on students’ entrepreneurial spirit of students after participating in the Market Day activity. This activity not only introduces basic entrepreneurial concepts such as planning, production, marketing, and sales but also develops students' soft skills, including teamwork, communication, creativity, and decision-making abilities.